Some Characteristics Of Ng-Groups - Faraj.A.Abdunabi; Ahmed shletiet; Muatazz.A.Bashir (Journal of Pure & Applied Sciences, 2022)
The This paper aims to consider and study some new properties in NG groups that consist of non-bijective transformations that are not a subset of symmetric groups. The regularity of these groups presents such as new results. Moreover, a new definition of anti-inverse NG groups is given. Some new results and properties are studied.